An iterative method for equilibrium problems and a finite family of relatively nonexpansive mappings in a Banach space - Cholamjiak P. (2014)
In this paper, we introduce a new iterative method for finding a common element of the set of fixed points of a finite family of relatively nonexpansive mappings and the set of solutions of an equilibrium problem in uniformly convex and uniformly smooth Banach spaces. Then we prove a strong convergence theorem by using the generalized projection. © 2010 Elsevier Inc. All rights reserved.